Elementos de la Competitividad en la pequeña y mediana empresa (PyMEs) Agrícolas del Distrito de Santa Marta (Caribe Colombiano) (2023)
The objective of this paper is to identify the elements of competitiveness in agricultural SMEs in the district of Santa Marta in the Colombian Caribbean. The target population is 97 SMEs, in each one a questionnaire was applied to the person responsible for carrying out the activities related to the production process. The collection was made based on the technique of the survey. This questionnaire is composed of a total of six items, structured with closed multiple-choice questions, with five Likert scale response alternatives. A score of 3.26 was obtained, which according to the classification of the scale is considered a neutral position, aspects that show an indifference to the elements that are related to technological development, lowering their levels of competitiveness against institutions of the same nature. © 2019.